Performance of lightweight concrete contain palm oil fuel ash towards elevated temperature subjected to air cooling - Izzati, Mohd Khalid (2018)
This study is about the effect of cooling method on the performance of lightweight concrete that contain palm oil fuel ash exposed to elevated temperature. The weight loss, crack, color and compressive strength of concrete containing palm oil fuel ash (POFA) as cement replacement after exposed to elevated temperature and air cooling method were investigated. In this study the concrete specimen are made from OPC and mixes of POFA concrete were prepared and subjected to different temperature. POFA were used as cement replacement due to the carbon dioxide produce through cement process which causes global warming. After water cured for 28 days the specimen were subjected to fire resistance test. Next, all the specimen will be place in the furnace electrical with increasing temperature of 200℃, 400℃, 600℃, 800℃ for 1 hour period. A total of difference percentage of POFA which are 0%,10%,20%,30%,40%.These specimen were subjected by air cooling method. The compressive strength was found higher in 10% of POFA concrete than the normal concrete. Meanwhile the weight loss is high in 40% of POFA concrete at 800℃.In addition, the higher the temperature, higher discolouration and cracking of the concrete.